Real-world cost of treatment for multiple sclerosis patients initiating and receiving infused disease-modifying therapies per recommended label in the United States. (2nd August 2020) - Nicholas, Jacqueline; Halpern, Rachel; Ziehn, Marina; Peterson-Brandt, Jesse; Leszko, Michael; Deshpande, Chinmay
Abstract: Aims: The study evaluated the real-world cost of treatment in multiple sclerosis (MS) patients initiating infused disease-modifying-therapies (DMT) in the United States. Materials and Methods: This retrospective cohort study using administrative claims data included adult patients with MS initiating index infusion DMT (ocrelizumab (OCR), natalizumab (NTZ) or alemtuzumab (ATZ)) from April 2017–September 2018 with 6-months pre/12-months post-index continuous enrollment. The primary cohort included patients who had prescribed annual dosing visits indicated by the approved product label (PL): 3 OCR, 5 ATZ, and 12–13 NTZ infusion visits within the first year of initiation. Annual treatment cost was the sum of all costs on index DMT infusion visit dates. Costs were summarized for a primary and secondary cohort of patients receiving additional doses than prescribed in PL (>3 OCR, >5 ATZ, and >13 NTZ infusion visits); and an overall cohort of patients who met minimum required annual dose (≥3 OCR, ≥5 ATZ, and ≥12 NTZ), further stratified by insurance type. Results: For patients in the primary cohort (123 OCR, 18 ATZ, and 48 NTZ), mean (standard-deviation) annual cost of treatment with OCR, ATZ, and NTZ cohorts was $72, 066 ($34, 480), $121, 053 ($51, 097) and $93, 777 ($38, 815), respectively. Among patients initiating OCR and NTZ, 15 and 6% respectively, had additional infusion visits leading to greater costs. Mean annual costs of index infusion DMT treatment in the overall cohort (162 patients treated with OCR, 18 with ATZ, 56 with NTZ) were $80, 582, $121, 053, and $93, 807, respectively. The mean costs for commercial enrollees were higher than those for MAPD enrollees. Limitations: Small sample size, limited population generalizability, and cost-reduction for ATZ beyond the second year need to be accounted for. Conclusions: Real-world infusion DMT treatment costs for commercially insured patients were higher than perceived expenditures based on wholesale acquisition cost and administration costs via a physician-fee schedule. Consideration of real-world costs in cost-effectiveness and treatment/coverage decisions is needed.